2009
DOI: 10.1007/s10620-009-0785-5
|View full text |Cite
|
Sign up to set email alerts
|

Alterations of Bone Marrow Sinusoidal Endothelium in Rat and Patients with Liver Cirrhosis

Abstract: Whether bone marrow changes occur and potentially contribute to the hematological abnormalities in liver cirrhosis remain unclear. In this study, we established a rat model of liver cirrhosis induced by carbon tetrachloride. Electron microscopy examination showed focal lesions in bone marrow sinusoidal endothelium and hematopoietic cells in animals with cirrhosis. With the persistence of liver cirrhosis, injuries of bone marrow sinusoidal endothelium progressed from mild mitochondrial changes to nuclear pycnos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 23 publications
0
8
0
Order By: Relevance
“…In a previous study, the ultrastructure of BMECs in rats with LF was observed to be altered (22). Furthermore, vWF, an endothelial cell injury biomarker, was increased compared with normal controls (22).…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…In a previous study, the ultrastructure of BMECs in rats with LF was observed to be altered (22). Furthermore, vWF, an endothelial cell injury biomarker, was increased compared with normal controls (22).…”
Section: Discussionmentioning
confidence: 93%
“…Furthermore, vWF, an endothelial cell injury biomarker, was increased compared with normal controls (22). In the process of vascular endothelial damage, vWF mediates leukocyte and platelet adhesion (23).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…If so, the excessive splanchnic angiogenic response induced by portal hypertension could be related to the embrionary colonization process by cells bearing a dual hemato-endothelial phenotype. In addition, there is evidence of the association between liver cirrhosis and bone marrow alterations in both rats and patients [79]. Inflammatory mediators may be responsible for increased expression of adhesion molecules in the bone marrow sinusoidal endothelium.…”
Section: The Angiogenic Phenotype: Remodeling Through Extraembryonic mentioning
confidence: 99%
“…Inflammatory mediators may be responsible for increased expression of adhesion molecules in the bone marrow sinusoidal endothelium. However, more investigation is needed to clarify the precise mechanism of how sinusoidal endothelium changes affect the hematopoietic cells [79]. Greater understanding is required pertaining to the relationship of portal hypertension with both processes, i.e., angiogenic and hematopoietic.…”
Section: The Angiogenic Phenotype: Remodeling Through Extraembryonic mentioning
confidence: 99%